2022
DOI: 10.1101/2022.11.02.22281819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy and Precision of 3D Optical Imaging for Body Composition and their Associations to Metabolic Markers by Age, BMI, and Ethnicity

Abstract: Background: Recent three-dimensional optical (3DO) imaging advancements have provided a more accessible, affordable, and self–operating opportunities for assessing body composition. 3DO is accurate and precise compared to clinical measures measured by dual–energy X–ray absorptiometry (DXA) in diverse study samples. However, the accuracy and precision of an overall 3DO body composition model in specific subgroups is unknown. Therefore, this study aimed to evaluate 3DOs accuracy and precision by subgroups of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…3DO can identify signals associated with muscle, bone, and frailty 13 . 3DO scanners use depth cameras to scan the surface of the body to provide accurate and precise automated anthropometry and a high-resolution 3D mesh 14,15 , which is used to create statistical shape models to predict body composition 13,[16][17][18][19] . A recent paper showed that reposing these meshes to a standardized pose before analysis improved the accuracy and precision regardless of initial pose 20 .…”
Section: Introductionmentioning
confidence: 99%
“…3DO can identify signals associated with muscle, bone, and frailty 13 . 3DO scanners use depth cameras to scan the surface of the body to provide accurate and precise automated anthropometry and a high-resolution 3D mesh 14,15 , which is used to create statistical shape models to predict body composition 13,[16][17][18][19] . A recent paper showed that reposing these meshes to a standardized pose before analysis improved the accuracy and precision regardless of initial pose 20 .…”
Section: Introductionmentioning
confidence: 99%
“…3DO can identify signals associated with muscle, bone, and frailty 13 . 3DO scanners use depth cameras to scan the surface of the body to provide accurate and precise automated anthropometry and a high-resolution 3D mesh 14,15 , which is used to create statistical shape models to predict body composition 13,[16][17][18][19] . A recent paper showed that reposing these meshes to a standardized pose before analysis improved the accuracy and precision regardless of initial pose 20 .…”
mentioning
confidence: 99%